In Vivo Imaging of MMP‐13 Activity Using a Specific Polymer‐FRET Peptide Conjugate Detects Early Osteoarthritis and Inhibitor Efficacy. (25th July 2018) - Duro‐Castano, Aroa; Lim, Ngee Han; Tranchant, Isabelle; Amoura, Mehdi; Beau, Fabrice; Wieland, Heike; Kingler, Otmar; Herrmann, Matthias; Nazaré, Marc; Plettenburg, Oliver; Dive, Vincent; Vicent, María J.; et al.
Abstract: Imaging early molecular changes in osteoarthritic (OA) joints is instrumental for the development of disease‐modifying drugs. To this end, a fluorescent resonance energy transfer‐based peptide probe that is cleavable by matrix metalloproteinase 13 (MMP‐13) has been developed. This protease degrades type II collagen, a major matrix component of cartilage. The probe exhibits high catalytic efficiency ( k cat / K M = 6.5 × 10 5 m −1 s −1 ) and high selectivity for MMP‐13 over a set of nine MMPs. To achieve optimal in vivo pharmacokinetics and tissue penetration, the probe has been further conjugated to a linearl ‐polyglutamate chain of 30 kDa. The conjugate detects early biochemical events that occur in a surgically induced murine model of OA before major histological changes. The nanometric probe is suitable for the monitoring of in vivo efficacy of an orally bioavailable MMP‐13 inhibitor, which effectively blocks cartilage degradation during the development of OA. This new polymer‐probe can therefore be a useful tool in detecting early OA, disease progression, and in developing MMP‐13‐based disease‐modifying drugs for OA. Abstract : An in vivo optical imaging probe comprised of a fluorescence resonance energy transfer (FRET) peptide specific for MMP13 conjugated to poly‐l ‐glutamic acid allows live in vivo imaging of disease‐related events. The nanometric probe detects early stages of the disease in a murine surgical model of osteoarthritis and provides real time readout on therapeutic efficacy of MMP13 inhibitors.